2022
DOI: 10.3389/fimmu.2022.868175
|View full text |Cite
|
Sign up to set email alerts
|

KIR- Ligand Interactions in Hypertensive Disorders in Pregnancy

Abstract: HypothesisThe activity of natural killer (NK) cells is considered an important factor for the tolerance of the fetus during pregnancy. The complications of pregnancy, such as hypertensive disorders (HDP), may be therefore associated with this immune compartment.MethodsThe current study included 41 pregnant women diagnosed with HDPs (Gestational Hypertension; GH or Preeclampsia; PE) and 21 healthy women. All the patients were under continuous obstetric care during the pregnancy and labour. The number of mother-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…It has also been postulated that impaired placentation and PE in general result from insufficient maternal tolerance to fetal alloantigens. This is in accordance with altered proportions and function of NK cell subsets in peripheral blood (3,6,(13)(14)(15) and placentas of women with PE (14,16). Similar changes were observed for decidual macrophages (17), dendritic cells (DC) (18), and T cells including an increased Th17/Treg ratio (19,20).…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…It has also been postulated that impaired placentation and PE in general result from insufficient maternal tolerance to fetal alloantigens. This is in accordance with altered proportions and function of NK cell subsets in peripheral blood (3,6,(13)(14)(15) and placentas of women with PE (14,16). Similar changes were observed for decidual macrophages (17), dendritic cells (DC) (18), and T cells including an increased Th17/Treg ratio (19,20).…”
Section: Introductionsupporting
confidence: 72%
“…In some patients (~25% of GH cases; 3-7% of all pregnancies), GH progresses into PE, which is associated with endothelial dysfunction and changes in the coagulative system that may lead to end-organ injury. The clinical manifestation of PE is usually characterized by proteinuria, elevated levels of liver enzymes, and epigastric pain being the consequence of liver dysfunction, low platelet counts, and/or neurological symptoms (3,5,6). Thus, it may contribute to maternal morbidity including renal failure, liver rupture, stroke, eclampsia, and death.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed that the killer immunoglobulin-like receptor (KIR), expressed on NK cells, is a key regulator of NK cell function and modulates NK cell activity by recognizing with specific human leukocyte antigen (HLA) molecules in the fetus, affecting maternal immune tolerance in the fetus, which influences the development of HDP ( 53 ). It was found that the absolute number of KIR ligand mismatches is significantly elevated in HDP and the homeostatic activation of NK cells affects the invasion of trophoblast cells into the uterine spiral arteries, leading to inadequate placental perfusion, so that KIR receptor-based diagnostics can be detected and used as a predictive HDP risk marker ( 54 ). However, studies on the specific regulation of the number, phenotype and function of dNK cells involved in the development of HDP are still at the stage of inference rather than evidence, further validation studies are still needed.…”
Section: Discussionmentioning
confidence: 99%